Unilateral cerebellar hypoplasia in a 9-year-old child with chronic granulomatous disease: A case report - Ali Hajihashemi, MD; Mahsa Geravandi, MD (Radiology Case Reports, 2023)
Unilateral cerebellar hypoplasia is a rare neurological condition that affects the development of the cerebellum, causing symptoms like poor coordination, balance issues, tremors, and speech problems. Unilateral cerebellar hypoplasia can occur as an isolated finding or as part of a larger neurological disorder or hereditary disease. There have been rare recorded instances where patients with chronic granulomatosis disease have been found to have neurological symptoms, such as brain abscesses or persistent inflammation, even though that CGD primarily affects the immune system and causes recurrent infections.A 9-year-old male with a known diagnosis of CGD presented to our neurology outpatient department with complaints of frequent falls and speech abnormalities. His parents described suspicious seizure-like movements and poor scholarly performance. Neurologic examination showed ataxic gait, slurred speech, and right-sided plantar extensor reflex. Initial laboratory findings were normal. MRI revealed marked reduced volume of the left cerebellar hemisphere with intact vermis and asymmetry of the posterior fossa. The residual left cerebellar hemisphere showed a normal folia and gray-white matter differentiation pattern. CSF filled the space created by the left hypoplastic cerebellum. A diagnosis of unilateral cerebellar hypoplasia was made.There is no known direct association between chronic granulomatous disease and unilateral cerebellar hypoplasia. However, more research is required to discover whether there is any connection between them. Although it is possible for a child to have CGD and UCH, managing such cases requires a multidisciplinary approach involving neurologists, immunologists, and other specialists to provide appropriate care and treatment.